The Implementation Of The Card Shift Method In PAI Learning Questions In Class V SDN 09 VII Koto Sungai Sarik Padang Pariaman - Muliyarti Muliyarti (Ruhama : Islamic Education Journal, 2021)
The trend in education today is to restore the point of view of student success in learning that will be successful if a conducive environment is created. Learning material will be easy to remember if students play a direct role in learning, not just listeners. In the past, students were often burdened with target material to train their memory. However it worked in the short term. Their memory will disappear over time. But things like this make students fail in solving problems every day.The core of the discussion that will be discussed in this research is, "How is the implementation of the question paper throwing method in Islamic Education learning?"In this study, researchers conducted action research which consisted of two phases. Each phase is divided into four stages, namely: design, implementation and observation, reflection, and improvement. The object studied was elementary school student no.09 VII Koto Sungai Sarik Semester two of the 2018/2019 academic year. The data obtained are in the form of formative test results, observation sheets of teaching and learning activities.Based on the results of data analysis, it can be concluded that student learning outcomes have increased from phase 1 to phase 2, namely, phase 1 (63.63%), phase 2 (81.81%).Thus, the learning system that uses the question-throwing method should be able to influence the learning motivation of elementary school students No. 09 VII Koto Sungai Sarik Even Semester Academic Year 2018/2019, and this learning model can be applied by Islamic Education teachers in learning in their class